2015
DOI: 10.18203/2320-1770.ijrcog20150952
|View full text |Cite
|
Sign up to set email alerts
|

Study of obstetric and fetal outcome of twin pregnancy in a tertiary care centre

Abstract: Background:The past two decades have witnessed a sharp rise in the incidence of twin and higher order gestations. The progress and developments in assisted reproductive technology, availability and widespread use of ovulation inducing drugs and delayed childbearing are thought to be the causes responsible for the rise. Twin pregnancy is associated with increased maternal and perinatal morbidity and mortality as well as healthcare costs. Maternal complications like hypertensive disorders, anemia, gestational di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…7 Important indications were fetal malpresentations and prev lscs which were the same indications in majority of the studies coated. 2,7 The mean birth weight of first twin was 1.8kg and second twin was 1.6kg which were similar to the studies done by Gurupreet Kaur et al, Chaudhary et al and Jacques Milliez MD et al [8][9][10] The low birth weight in the present study could be due to nutritional factors, low socioeconomic factors and increased prevalence of preterm labour.…”
Section: Discussionsupporting
confidence: 90%
“…7 Important indications were fetal malpresentations and prev lscs which were the same indications in majority of the studies coated. 2,7 The mean birth weight of first twin was 1.8kg and second twin was 1.6kg which were similar to the studies done by Gurupreet Kaur et al, Chaudhary et al and Jacques Milliez MD et al [8][9][10] The low birth weight in the present study could be due to nutritional factors, low socioeconomic factors and increased prevalence of preterm labour.…”
Section: Discussionsupporting
confidence: 90%
“…Deepthi et al and Nandmer G et al reported preterm delivery in 60% and 67% of twin pregnancies respectively. 14,17 Whereas, Shetty MB et al and Chowdhury et al reported much lower incidence of preterm delivery in 38% and 44% of patients respectively. 18,19 The inherited risk of preterm delivery in multiple pregnancies is supported by higher incidence of preterm delivery in this study, out of 304 (70%) preterm delivery 272 (89.4% had spontaneous preterm labor and 32 (10.5%) were induced preterm delivery.…”
Section: Discussionmentioning
confidence: 96%
“…Studies have reported cesarean section (LSCS) in 68%, 49% and 45% where as our study reports it as 92%. [27][28][29][30][31] In our study most common mode of delivery is LSCS , few studies reported that mode of delivery is a significant predictor of perinatal outcome , however this predictor is not quite conclusive, as conflicting results are published in other few studies. 31,32 Pregnancy induced hypertension(PIH) was observed in 32% twin pregnancy in our study which was similar to study published earlier which reported 40 % PIH.…”
Section: Discussionmentioning
confidence: 92%